Pearl millet cultivars developed for A1 zone - Singh, S P; S, Mukesh Sankar; Satyavathi, C Tara (Indian Farming, 2018)
Hybrids can be spread in this region, if seeds of hybrids can be made available to farmers at cheaper rate around Rupees 120/ kg or same price for OPVs. State seed corporations of Rajasthan, Haryana and Gujarat should strengthen the hybrid seed production for A1 zone for meeting the demand of hybrid seed at reasonable price. Private sector should also adopt more sympathetic approach for solving the problem of hybrid seed production in this harsh zone.